Emergence of a STAT3 mutated NK clone in LGL leukemia. Issue 1 (2015) - Yan, Yiyi; Olson, Thomas L.; Nyland, Susan B.; Feith, David J.; Loughran, Thomas P.
Abstract: Large granular lymphocyte (LGL) leukemia is a chronic clonal lymphoproliferative disorder. Here, a T-LGL leukemia patient developed NK-LGL leukemia with residual leukemic T-LGL. TCRVβ usage and CDR3 sequence drifts were observed with disease progression. A STAT3 S614R mutation was identified in NK but not T-cells in the mixed leukemic stage. Multiple, non-dominant T-cell clones with distinct STAT3 mutations were present throughout. Our results suggest that T and NK-LGL leukemia may share common pathogenesis mechanisms and that STAT3 mutation alone is insufficient to bring about clonal expansion. Mutational and immunological monitoring may provide diagnostic and therapeutic significance in LGL leukemia. Highlights: Coexistence of NK and T cell clones in LGL leukemia. Demonstration for the first time of a shift from T-LGL to NK type of LGL leukemia. Emergence of a dominant STAT3-mutated clone in NK cells during disease progression. Presence of additional STAT3-mutated clones that fail to become dominant over time.